Pathology in practice : diseases and dissections in early modern Europe - Bresadola, Marco; Conforti, Maria; De Renzi, Silvia (New York : Routledge, 2018)
"Post-mortems may have become a staple of our TV viewing, but the long history of this practice is still little known. This book provides a fresh account of the dissections that took place across early modern Europe on those who had died of a disease or in unclear circumstances. Drawing on different approaches and on sources as varied as notes taken at the dissection table, legal records and learned publications, the chapters explore how autopsies informed the understanding of pathology of all those involved. With a broad geography, including Rome, Amsterdam and Geneva, the book recaptures the lost worlds of physicians, surgeons, patients, families and civic authorities as they used corpses to understand diseases and make sense of suffering. The evidence from post-mortems was not straightforward, but between 1500 and 1750 medical practitioners rose to the challenge, proposing various solutions to the difficulties they encountered and creating a remarkable body of knowledge. The book shows the scope and diversity of this tradition and how laypeople contributed their knowledge and expectations to the wide-ranging exchanges stimulated by the opening of bodies."--Provided by publisher.
Pathological dissections in early modern Europe : practice and knowledge / Silvia De Renzi, Marco Bresadola and Maria Conforti -- Humanist post-mortems : philology and therapy / Gionata Liboni -- Organising pathological knowledge : Theophile Bonet's sepulchretum and the making of a tradition / Massimo Rinaldi -- The problems of anatomia practica and how to solve them : pathological dissection around 1700 / Marco Bresadola -- Post-mortems, anatomical dissections and humoural pathology in the sixteenth and early seventeenth centuries / Michael Stolberg -- Seats and series : dissecting diseases in the seventeenth century / Silvia De Renzi -- Visible signs, invisible processes : explaining poison in the late seventeenth century / Maria Conforti -- Frederik Ruysch, surgical anatomy and the Amsterdam Republic of medicine / Rina Knoeff -- Pre- and post-mortem inquiries : assessing poisoning in the law courts of sixteenth-century Rome / Elisa Andretta -- Dissecting pain : patients, families and medical expertise in early modern Germany / Annemarie Kinzelbach -- Therapeutic post-mortems in and around eighteenth-century Geneva / Philip Rieder.
Keywords: Pathology -- History; Medicine -- History